Enhancing teacher capacity and parental engagement during the covid-19 pandemic at ABA Kindergarten - Resti Yulianti Sutrisno; Sutantri Sutantri; Pramitha Sari; Titih Huriah; Yanuar Fahrizal; Rausan Fikri Priyana Putra; Bertha Tesma Wulandari; Siti Nenti Sarifah (Community Empowerment, 2024)
The Covid-19 pandemic necessitates teachers to be creative in conducting learning. Based on preliminary studies, the problem faced by ABA Kindergarten is the lack of teacher ability in creating attractive and innovative online teaching media. Additionally, forums for parents are still limited regarding how to prepare for safe learning in the pandemic era. The aim of this service is to enhance teacher capacity in creating online teaching media and increase knowledge in preparing for safe offline (face-to-face) learning during the pandemic. The service methods used include: 1) workshop on making online teaching media for teachers, and 2) parenting seminar for parents, teachers, and cadres. The results of the first program showed an increase in teachers' abilities in creating online teaching media, with all participants being able to create online learning videos and upload it to YouTube. The results of the second program revealed good knowledge regarding preparation for offline learning, with an average posttest score for health preparation (77.8), nutritional preparation (94.4), and anticipating gadget addiction (94.4).